Perancangan Sistem Informasi Laporan Pembayaran Iuran Komite Pada SMK Negeri 1 Kota Sorong - Wattimena, Juneth N.; Sigit, Ryandy Nur; Manuputty, Peter (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
SMK Negeri 1 Sorong City is one of the largest vocational high schools in Sorong City, Southwest Papua. Management of committee dues payment reports at SMK Negeri 1 Sorong City is still very manual, namely by recording using book. This matter results in various problems, such as frequent damage to data storage media, errors in data recording and data loss, which hinders financial reporting. In this research, data collection was carried out through two types of data, namely primary data and secondary data. The waterfall method is the system development method used in this research. Program modeling tools, namely UML, include use case diagrams. The test used in this research is black box testing. The conclusion of this research is a web based committee dues payment reporting information system can be used as an efficient medium for reporting committee dues payment transactions.